Anonymous and Efficient Message Authentication Scheme for Smart Grid. (12th May 2019) - Wu, Libing; Wang, Jing; Zeadally, Sherali; He, Debiao
Abstract : Smart grid has emerged as the next-generation electricity grid with power flow optimization and high power quality. Smart grid technologies have attracted the attention of industry and academia in the last few years. However, the tradeoff between security and efficiency remains a challenge in the practical deployment of the smart grid. Most recently, Li et al. proposed a lightweight message authentication scheme with user anonymity and claimed that their scheme is provably secure. But we found that their scheme fails to achieve mutual authentication and mitigate some typical attacks (e.g., impersonation attack, denial of service attack) in the smart grid environment. To address these drawbacks, we present a new message authentication scheme with reasonable efficiency. Security and performance analysis results show that the proposed scheme can satisfy the security and lightweight requirements of practical implementations and deployments of the smart grid.